0
$\begingroup$

I'm new to boolean algebra and having problems simplifying expressions with odd number terms,

Expressions such as:

1.

A'B'C'D + A'B'CD + AB'C'D + AB'CD + ABC'D

2.

A'BC + AB'C' + A'B'C' + AB'C + ABC

Here is my logic for both expressions:

A'B'C'D + A'B'CD + AB'C'D + AB'CD + ABC'D

A'B'D'(C+C') + AB'D(C+C') + ABC'D

A'B'D + AB'D + ABC'D

B'D(A'+A) + ABC'D

B'D + ABC'D

I never touch the last term, and I don't know what rule I'm missing. Same thing happens on the second expression:

A'BC + AB'C' + A'B'C' + AB'C + ABC

A'BC + B'C'(A+A') + AC(B'+B)

A'BC + B'C + AC

Again, one term untouched..

For 1. the result should be AC'D + B'D

For 2. the result should be B'C + BC + AC

I could maybe use Karnaugh maps but I also would like to understand the algebra logic.

$\endgroup$
1
$\begingroup$

It’s not too hard to check the results after you know them:

$$\begin{align*}B'D+ABC'D&=(B'+ABC')D\\ &=(B'+AB'C'+ABC')D\\ &=\Big(B'+A(B'+B)C')\Big)D\\ &=(B'+AC')D\\ &=B'D+AC'D \end{align*}$$

and

$$\begin{align*}A'BC + B'C + AC&=B'C+(A'B+A)C\\ &=B'C+(A'B+A+AB)C\\ &=B'C+\Big(A+(A'+A)B\Big)C\\ &=B'C+(A+B)C\\ &=B'C+AC+BC\;. \end{align*}$$

That second one can be further simplified to $AC+C=C$, since $B'C+BC=(B'+B)C=C$.

In both calculations I used the absorption law: $B'=B'+AB'C'$ in the first, and $A=A+AB$ in the second.

When you have no more than three or four proposition letters, you may find Venn diagrams helpful.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.